The impact of digitization on the strategic growth in the banking sector using consolidated bank of ghana as a case study - ADAMAH GEORGE QUAYEFIO (KNUST, 2024)
The study examined the impact of digitization on the strategic growth in the banking sector using Consolidating Bank of Ghana. The sample size of the study was 200 staff from Consolidated Bank of Ghana out of the 350 population size. The study issued the structured close-ended questionnaire to collect the data from the respondents. The study used the SPSS version 21.0 to analyse the data and presented in tables showing the means and standard deviation. The study found out that, pertaining the levels of digitization of banks, it can be mentioned that the bank has a high quality website, strong social media presence, robust search engine optimization mechanism and also proper planning for email marketing. Furthermore it was identified that the bank shares content across several online platforms and also has a platform for blogging to engage with audience and expand beyond only product sales. Finally, it was mentioned that banks have a computerized customer service and also practice digital advertising. The study also revealed that, there is a positively significant relationship between digitization and performance of banks in Ghana. With this, the study found out that the bank has expanded its client base due to the digital structures. Also, the bank conducts SWOT analysis often to measure strategic growth. Again, the bank has gained new opportunities in the banking industry as a result of the introduction of digitation. Finally, the bank has been able to broaden its horizon since it has been able to penetrate into other regions in Ghana.